(untitled) (Journal of Dhaka National Medical College & Hospital, 2023)
Background: Heart failure is undoubtedly one of the most challenging health problems. In critical illness, thyroid hormone dysregulation occurs in heart failure patients without apparent thyroid disease, ultimately decrease in triiodothyronine level which accelerates poor prognosis of the patients. Objective: To determine the status of serum FT3& TSHin patients with heart failure. Methods: This was a cross-sectional analytical study, carried out in the Department of Biochemistry, Sir Salimullah Medical College, Dhaka from March 2022 to February 2023. A total number of 110 clinically diagnosed heart failure subjects who were admitted within 6 hours at Cardiology department of SSMC & MH and NICVD, according to inclusion and exclusion criteria were included in this study. Serum FT3 and serum TSH were determined. Results: Heart failure prevalence increases from 61-70 years and almost two third of patients were male.Serum FT3 level was significantly lower among heart failure patients but serum TSH was normal in all study subjects. Conclusion: Low FT3 is associated with heart failure and contributes to the worsening or exacerbation of heart failure. J. Dhaka National Med. Coll. Hos. 2023; 29 (02): 38-41